Effect of Immunosuppressive Agents on Hepatocyte Apoptosis Post-Liver Transplantation. - Eu Jin Lim; Ruth Chin; Ueli Nachbur; John Silke; Zhiyuan Jia; Peter W Angus; Joseph Torresi (PLoS ONE, 2015)
Immunosuppressants are used ubiquitously post-liver transplantation to prevent allograft rejection. However their effects on hepatocytes are unknown. Experimental data from non-liver cells indicate that immunosuppressants may promote cell death thereby driving an inflammatory response that promotes fibrosis and raises concerns that a similar effect may occur within the liver. We evaluated apoptosis within the liver tissue of post-liver transplant patients and correlated these findings with in vitro experiments investigating the effects of immunosuppressants on apoptosis in primary hepatocytes.Hepatocyte apoptosis was assessed using immunohistochemistry for M30 CytoDEATH and cleaved PARP in human liver tissue. Primary mouse hepatocytes were treated with various combinations of cyclosporine, tacrolimus, sirolimus, or MMF. Cell viability and apoptosis were evaluated using crystal violet assays and Western immunoblots probed for cleaved PARP and cleaved caspase 3.Post-liver transplant patients had a 4.9-fold and 1.7-fold increase in M30 CytoDEATH and cleaved PARP compared to normal subjects. Cyclosporine and tacrolimus at therapeutic concentrations did not affect hepatocyte apoptosis, however when they were combined with MMF, cell death was significantly enhanced. Cell viability was reduced by 46% and 41%, cleaved PARP was increased 2.6-fold and 2.2-fold, and cleaved caspase 3 increased 2.2-fold and 1.8-fold following treatment with Cyclosporine/MMF and Tacrolimus/MMF respectively. By contrast, the sirolimus/MMF combination did not significantly reduce hepatocyte viability or promote apoptosis.Commonly used immunosuppressive drug regimens employed after liver transplantation enhance hepatocyte cell death and may thus contribute to the increased liver fibrosis that occurs in a proportion of liver transplant recipients.